Model systems for the study of Enterococcal colonization and infection - Goh, H. M. Sharon; Yong, M. H. Adeline; Chong, Kelvin Kian Long; Kline, Kimberly A. (Virulence, 2017)
Enterococcus faecalis and Enterococcus faecium are common inhabitants of the human gastrointestinal tract, as well as frequent opportunistic pathogens. Enterococci cause a range of infections including, most frequently, infections of the urinary tract, catheterized urinary tract, bloodstream, wounds and surgical sites, and heart valves in endocarditis. Enterococcal infections are often biofilm-associated, polymicrobial in nature, and resistant to antibiotics of last resort. Understanding Enterococcal mechanisms of colonization and pathogenesis are important for identifying new ways to manage and intervene with these infections. We review vertebrate and invertebrate model systems applied to study the most common E. faecalis and E. faecium infections, with emphasis on recent findings examining Enterococcal-host interactions using these models. We discuss strengths and shortcomings of each model, propose future animal models not yet applied to study mono- and polymicrobial infections involving E. faecalis and E. faecium, and comment on the significance of anti-virulence strategies derived from a fundamental understanding of host-pathogen interactions in model systems.